Teaching vocabulary for English language learners (Journal of Science-Innovative Research in Uzbekistan, 2024)
Teaching vocabulary to English Language Learners (ELLs) is crucial for their language development and overall success in academic and social settings. This research explores strategies for teaching vocabulary to ELLs, focusing on differentiating between active and passive vocabulary and introducing various vocabulary techniques